A new era for studies on cross-Strait relations: introduction - Lee, Chun-Yi (SAGE Publications, 2013)
After more than half a century’s separation, interaction between China and Taiwan has increased and has progressively changed from a politico-economic interaction to a more civic interaction. Scholars working on cross-Strait relations have recently begun to pay attention to the civic influence of Taiwanese businesses on the relationship. Some emphasize the importance of sub-governmental interactions in the process of cross-Strait integration. Others assert that Taiwanese businesses can exercise economic leverage to constrain the Chinese government in cross-Strait policymaking. These scholars stress bottom–up processes by observing current phenomena, then deducing the emerging pattern of cross-Strait relations that may be influenced by business activities. Taking account of changing trends in scholarly discussions of the cross-Strait relationship, this special issue of China Information presents current research in this field. Unlike studies on top–down processes that affect political and economic interactions between China and Taiwan, several contributions in the special issue highlight bottom–up mechanisms affecting such interactions by examining the identity of Taiwanese businesspeople and migrants, as well as the activities and implications of Taiwanese charitable organizations operating in China. This issue focuses not only on the impact of China on Taiwan, but also the impact of Taiwanese investments, migrants, and exports on Chinese society.